2005
DOI: 10.1111/j.0022-1112.2005.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of regulated discharge on burbot migration

Abstract: Burbot Lota lota movement and river discharge were studied in the Kootenai River, Idaho, U.S.A. and British Columbia, Canada, downstream of Libby Dam, Montana, U.S.A. A total of 24 adult burbot with transmitters were tracked from 1994 to 2000, for analysis of a travel distance of !5 km in 10 days termed 'stepwise movement'. Of 44 'stepwise movements', significantly greater movements during pre-spawning and spawning were observed when average daily discharges from Libby Dam were <300 m 3 s À1 , with a mean of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 17 publications
3
32
1
Order By: Relevance
“…In our study, total movement distances were greater than the movement of wild burbot monitored during previous studies in the Kootenay River drainage (Paragamian 2000;Dunigan and Sinclair 2008;Paragamian and Wakkinen 2008) but were similar to the results of studies documenting riverine migrations of burbot in other systems (Breeser et al 1988). Directed movement in this study was rapid in comparison with the findings of Paragamian et al (2005), who reported average travel rates of 3.36 km/d for wild adult burbot. However, movement distances of up to 125 km have been documented in Alaskan rivers, where one-way directed movements as high as 7.8 km/d were recorded (Breeser et al 1988).…”
Section: Discussionsupporting
confidence: 81%
“…In our study, total movement distances were greater than the movement of wild burbot monitored during previous studies in the Kootenay River drainage (Paragamian 2000;Dunigan and Sinclair 2008;Paragamian and Wakkinen 2008) but were similar to the results of studies documenting riverine migrations of burbot in other systems (Breeser et al 1988). Directed movement in this study was rapid in comparison with the findings of Paragamian et al (2005), who reported average travel rates of 3.36 km/d for wild adult burbot. However, movement distances of up to 125 km have been documented in Alaskan rivers, where one-way directed movements as high as 7.8 km/d were recorded (Breeser et al 1988).…”
Section: Discussionsupporting
confidence: 81%
“…Dreissenid mussels (Dreissena sp.) We suggest continued monitoring of burbot, particularly because it is of conservation concern in much of its range (Stapanian et al 2009) and it has been shown to be an excellent indicator of environmental change (e.g., Herrmann et al 1993;Tammi et al 1999;Paragamian et al 2000Paragamian et al , 2005Jackson et al 2008;Paragamian & Wakkinen 2008). Although water clarity more than doubled in nearshore areas of the eastern basin by 1993 as a result of dreissenid activity, there was no apparent temporal trend and considerable variation in water clarity during 1993-2003 (Barbiero & Tuchman 2004).…”
Section: Discussionmentioning
confidence: 93%
“…Burbot has been shown to be vulnerable to many environmental changes, particularly dams (Paragamian 2000b;Paragamian et al 2000Paragamian et al , 2005Paragamian & Wakkinen 2008), warming water temperatures (Jackson et al 2008), pollution (Herrmann et al 1993;Tammi et al 1999) and establishment of nonnative species (Berst & Spangler 1973;Christie 1973;Wells & McLain 1973;Baldwin et al 2002). Burbot has been shown to be vulnerable to many environmental changes, particularly dams (Paragamian 2000b;Paragamian et al 2000Paragamian et al , 2005Paragamian & Wakkinen 2008), warming water temperatures (Jackson et al 2008), pollution (Herrmann et al 1993;Tammi et al 1999) and establishment of nonnative species (Berst & Spangler 1973;Christie 1973;Wells & McLain 1973;Baldwin et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…environment, thermal anomalies and significant overfishing, a regular decrease in the population of burbot within the entire area of its appearance has been observed (Paragamian et al 2005Hardy et al 2008). In Poland, this species is included in the Red list of freshwater ichthyofauna of Poland (Witkowski et al 1999).…”
mentioning
confidence: 98%